2018
DOI: 10.20471/acc.2018.57.04.02
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Different Methods for Tigecycline Susceptibility Testing in Acinetobacter Baumannii

Abstract: SUMMARY – Tigecycline susceptibility testing (TST) presents a tremendous challenge for clinical microbiologists. Previous studies have shown that the Epsilometer test (E-test) and Vitek 2 automated system significantly overestimate the minimum inhibitory concentrations for tigecycline resistance compared to the broth microdilution method (BMM). This leads to very major errors or false susceptibility (i.e. the isolate is called susceptible when it is actually resistant). The aim of this study was to compare E-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Bedenic et al . have reported that AGT (E-test) did not provide reliable results ( 14 ). Interestingly, Akın et al .…”
Section: Discussionmentioning
confidence: 99%
“…Bedenic et al . have reported that AGT (E-test) did not provide reliable results ( 14 ). Interestingly, Akın et al .…”
Section: Discussionmentioning
confidence: 99%
“…The data were rendered as the mean AE standard deviation. resistant Gram-negative bacteria or carbapenemase-producing bacteria (Bedenic et al 2018). MCR-1 has attracted widespread global attention because it is a plasmid-mediated resistance gene that can cause bacterial resistance to polymyxins.…”
Section: Discussionmentioning
confidence: 99%
“…This has gradually led to some antibiotics becoming unsuccessful in clinical treatment and limits the choice of treatment options. Because of resistance to common antibiotics, polymyxin B and colistin (polymyxin E) are used as the last‐resort antibiotics to treat infections associated with multidrug‐resistant Gram‐negative bacteria or carbapenemase‐producing bacteria (Bedenic et al 2018). MCR‐1 has attracted widespread global attention because it is a plasmid‐mediated resistance gene that can cause bacterial resistance to polymyxins.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics such as tigecycline (TGC) and colistin (COL) are used as a last resort for the treatment of diseases caused by MDR bacteria. Since their recent reinstallation in clinical practice, TGC- and COL-resistant microbial isolates have already been reported ( 4 , 5 ). Ceftazidime-avibactam (CZA), a cephalosporin–β-lactamase inhibitor combination with a broad antibacterial spectrum, was introduced in 2015 and is regarded as a last-resort antibiotic ( 6 ).…”
Section: Introductionmentioning
confidence: 99%